Fetuin‐A‐containing calciprotein particle levels can be reduced by dialysis, sodium thiosulphate and plasma exchange. Potential therapeutic implications for calciphylaxis?. Issue 11 (23rd October 2013) - Cai, Michael MX; Smith, Edward R; Brumby, Catherine; McMahon, Lawrence P; Holt, Stephen G
Abstract: Calciprotein particles (CPP) are a novel marker of mineral stress. High levels of CPP are found in patients with calciphylaxis, a condition associated with marked vascular calcification and a poor prognosis. We report substantial reductions in CPP levels in a dialysis patient having combined haemodialysis (HD) and plasma exchange (PEx) prior to an ABO‐incompatible kidney transplant. We also report the effects of the same treatments combined with sodium thiosulphate (STS) in a patient newly diagnosed with calciphylaxis. Combining HD with intra‐dialytic STS and PEx we achieved a significant reduction in CCP with the least rebound between treatment sessions. After 6 weeks of treatment, the CPP reduction was paralleled by clinical improvement. Measurement of CPP may be an attractive marker for monitoring the effectiveness of calciphylaxis therapy.